Emergomycosis, an Emerging Systemic Mycosis in Immunocompromised Patients: Current Trends and Future Prospects - Samaddar, Arghadip; Sharma, Anuradha (Frontiers in Medicine, 2021)
Recently, the global emergence of emergomycosis, a systemic fungal infection caused by a novel dimorphic fungus Emergomyces species has been observed among immunocompromised individuals. Though initially classified under the genus Emmonsia, a taxonomic revision in 2017 based on DNA sequence analyses placed five Emmonsia-like fungi under a separate genus Emergomyces. These include Emergomyces pasteurianus, Es. africanus, Es. canadensis, Es. orientalis, and Es. europaeus. Emmonsia parva was renamed as Blastomyces parvus, while Emmonsia crescens and Emmonsia sola remained within the genus Emmonsia until a taxonomic revision in 2020 placed both the species under the genus Emergomyces. However, unlike other members of the genus, Emergomyces crescens and Emergomyces sola do not cause disseminated disease. The former causes adiaspiromycosis, a granulomatous pulmonary disease, while the latter has not been associated with human disease. So far, emergomycosis has been mapped across four continents: Asia, Europe, Africa and North America. However, considering the increasing prevalence of HIV/AIDS, it is presumed that the disease must have a worldwide distribution with many cases going undetected. Diagnosis of emergomycosis remains challenging. It should be considered in the differential diagnosis of histoplasmosis as there is considerable clinical and histopathological overlap between the two entities. Sequencing the internal transcribed spacer region of ribosomal DNA is considered as the gold standard for identification, but its application is compromised in resource limited settings. Serological tests are non-specific and demonstrate cross-reactivity with Histoplasma galactomannan antigen. Therefore, an affordable, accessible, and reliable diagnostic test is the need of the hour to enable its diagnosis in endemic regions and also for epidemiological surveillance. Currently, there are no consensus guidelines for the treatment of emergomycosis. The recommended regimen consists of amphotericin B (deoxycholate or liposomal formulation) for one to two weeks, followed by oral itraconazole for at least 12 months. This review elaborates the taxonomic, clinical, diagnostic, and therapeutic aspects of emergomycosis. It also enumerates several novel antifungal drugs which might hold promise in the treatment of this condition and therefore, can be potential areas of future studies.